PENGARUH AIR REBUSAN DAUN SALAM (Eugenia polyantha wight) TERHADAP PERTUMBUHAN Enterococcus faecalis - Rachmi Fanani Hakim; Fakhrurrazi Fakhrurrazi; Wahyuda Ferisa (Journal of Syiah Kuala Dentistry Society, 2016)
Entrerococcus faecalisis one of oral normal flora that has the ability to invaded into the tubules dentin and able to survive in acidic and alkaline environments within the root canal.Bay leaves is one kind of medicine antimicrobial plant that have chemical constituents such as tannins, flavonoids, essential oils, steroids, saponins and alkaloids.The purpose of this study was to determine the effect of water stewed of leaves at the concentration of 50%, 75% and 100% of the bacteria Entrerococcus faecalis. Entrerococcus faecalis that have been cultured in CHROM VRE Base Vorcomicyn was incubated at 37C anaerobically. Entrerococcus faecalis that have been cultured and identified exposed to the bay leavesstew water by standard plate count method on MHA. The results of statistical analysis using one-way ANOVA available the value of p = 0,000 (p 0,05), so can be concluded that stew water bay leaves has effect on Entrerococcus faecalis growth. The effect of Stewed Water Bay Leaves on Enterococcus faecalis was increased, by increasing itsconsentration 50%, 75%, and 100% in a row.Keyword: Antibacterial, Entrerococcus Faecalis, Stew Of Bay Leaves